2002
DOI: 10.1523/jneurosci.22-11-04540.2002
|View full text |Cite
|
Sign up to set email alerts
|

Slit2, a Branching–Arborization Factor for Sensory Axons in the Mammalian CNS

Abstract: Axons that carry information from the sensory periphery first elongate unbranched and form precisely ordered tracts within the CNS. Later, they begin collateralizing into their proper targets and form terminal arbors. Target-derived factors that govern sensory axon elongation and branching-arborization are not well understood. Here we report that Slit2 is a major player in branching-arborization of central trigeminal axons in the brainstem. Embryonic trigeminal axons initially develop unbranched as they form t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 59 publications
3
61
0
Order By: Relevance
“…We also studied the central afferent branching of sensory neurons, because Slits have been proposed to control central collateral formation and have been shown to stimulate trigeminal ganglia to sprout collaterals into the brainstem in an organotypic culture (Ozdinler and Erzurumlu, 2002). However, we did not observe any clear defects in the formation of central collateral branches inside the spinal cord.…”
Section: Slit/robo Signaling Is Also Required For Proper Bifurcation mentioning
confidence: 84%
See 1 more Smart Citation
“…We also studied the central afferent branching of sensory neurons, because Slits have been proposed to control central collateral formation and have been shown to stimulate trigeminal ganglia to sprout collaterals into the brainstem in an organotypic culture (Ozdinler and Erzurumlu, 2002). However, we did not observe any clear defects in the formation of central collateral branches inside the spinal cord.…”
Section: Slit/robo Signaling Is Also Required For Proper Bifurcation mentioning
confidence: 84%
“…Using dorsal root ganglion (DRG) cell cultures, we found that an N-terminal fragment of Slit2 (Slit2N) stimulated branching and elongation of rat DRG axons from embryonic day 14 (E14) when they normally arborize in their targets in vivo. Evidence to support this branching effect was also obtained using a trigeminal ganglion explant culture (Ozdinler and Erzurumlu, 2002) and by misexpression in zebrafish (Yeo et al, 2004). In the CNS, Slit1 was shown to regulate cortical dendritic branching in vitro (Whitford et al, 2002).…”
Section: Introductionmentioning
confidence: 79%
“…We recently reported that a member of the Slit family of proteins, Slit2, can induce arborization of central trigeminal axons at a time when they are in the elongation phase (Fig. 5) (Ozdinler and Erzurumlu, 2002). There are at least three members of the Slit family (Slit1, Slit2, Slit3) and three members of the Robo family, Robo1, Robo2, Robo3Rig1 (Rajagopalan et al, 2000;Simpson et al, 2000), which bind Slits.…”
Section: Axon Guidance and Arborization Signals For Developing Trigemmentioning
confidence: 99%
“…It is currently unknown how expression of the DUTTI mutant results in this phenotype, although a likely explanation is that normal signals transduced by ROBO1 are perturbed, either through inappropriate interactions with SLIT, or another ROBO receptor, or an as yet unidentified co-factor. In the nervous system, SLIT signals through ROBO to promote axon branching (Ozdinler and Erzurumlu, 2002;, therefore one possibility is that these irregularly shaped bronchioles are a result of inappropriate branching. This possibility, however, has not been directly tested, and additional data that could aid the interpretation of this phenotype, such as lung defects in other Slit or Robo null mice, have not yet been reported.…”
Section: Lung Branching Morphogenesis: Push-pull Mechanism Of Netrinsmentioning
confidence: 99%